Integrating Content Via Tik Tok in Maximizing English Proficiency - Rullu, ST. Marhana; Hardianti; Mukmin; Nurhaida Lakuana; Nurvina Tulo (International Journal of English Language and Pedagogy, 2024)
In today’s digital age, the integration of content via platforms like TikTok holds immense potential for maximizing English proficiency among learners, offering engaging and interactive opportunities for language. The study aims to investigated the effectiveness of integrating content via TikTok platform in maximizing English proficiency at SMP Negeri 3 Bulagi. Utilizing a qualitative method, this study will explore how content provided through TikTok can be optimally utilized to enhance English Language skills among learners. The subjects of this research are English teacher and grade 8 students. The methodology involves data collection through observation of TikTok usage as a language learning toll, interview with participant actively using the platform, and analysis of available content. The findings of this research are expected to provide deep insight into the potential of TikTok as an innovative and effective language learning tool, as well as practical guidance for educator and learners in leveraging this platform optimally to enhance English language proficiency. Based on the data obtained, integrating content via TikTok in language learning give many contributions in maximizing English proficiency. The first utilizing audio visual in TikTok application in language learning especially listening, Second, by using TikTok students can also process words to express, convey an express intention, ideas and thoughts feeling that compiled and developed according to the needs of students, Third, the edit feature contained in TikTok can be used by students presenting data, ideas or impressions in the form of a description of an object. Fourth the TikTok application can be used as a medium for students to practice reading news.